Scientific data (Nature Publishing Group, 2014)
Scientific Data, a peer-reviewed, online-only, open-access publication, publishes datasets that might not normally get into the open and increases the discoverability and reusability of datasets. Data Descriptors, the primary article type, describe previously unpublished datasets and expand on previous publications.
Keywords: věda a výzkum; Data Collection; sběr dat; data mining; Information Storage and Retrieval; Data Mining; ukládání a vyhledávání informací